2012
DOI: 10.1190/geo2011-0426.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling compaction effects on the elastic properties of clay-water composites

Abstract: Modeling the elastic properties of clay-bearing rocks (shales) requires thorough knowledge of the mineral constituents, their elastic properties, pore space microstructure, and orientations of clay platelets. Information about these variables and their complex interrelationships is rarely available for real rocks. We theoretically modeled the elastic properties of synthetic clay-water composites compacted in the laboratory, including estimates of pore space topology and percolation behavior. The mineralogy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…n = 1 for 1 st order reflections). This gave d ≈ 10•7 Å, which appears consistent with the expected basal spacing for a smectite without hydration (Bergaya et al 2006, Moyano et al 2012, Villar et al 2012.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…n = 1 for 1 st order reflections). This gave d ≈ 10•7 Å, which appears consistent with the expected basal spacing for a smectite without hydration (Bergaya et al 2006, Moyano et al 2012, Villar et al 2012.…”
Section: Resultssupporting
confidence: 78%
“…Hence, the results obtained here for gMgSm agreed reasonably well with previously published results for compacted clays [Vanorio et al 2003, Mondol et al2007, Moyano et al 2012 and were somewhat larger than expected for sMCC, based on data previously reported by Han et al [2011]. The smaller modulus of sMCC suggests that it should exhibit greater strain during loading and unloading than gMgSm, which is counter to the observations.…”
Section: Bulk Compaction Behavioursupporting
confidence: 92%
“…Several modeling approaches, assuming shale as a transverse isotropic body, have been proposed to explain anisotropic elastic properties, including selfconsistent theories and hypothetical assumptions of microstructures and preferred orientation (e.g., Rundle and Schuler, 1981;Hornby et al, 1994;Jakobsen et al, 2000;Draege et al, 2006;Ortega et al, 2007;Moyano et al, 2012). Although providing qualitatively convincing results, most of these modeling approaches have not fully taken clay preferred orientations, elastic anisotropy of minerals, and microstructural information into account.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, 2D sections of a core sample are used as the basis for statistical estimation of the aspect ratio for a given rock sample. One recent example can be found in Moyano et al (2012), where histograms of pore aspect ratio are estimated based on 2D sections from several clay samples. Gupta et al (2011) estimate aspect ratios ranging from 9 to 165 for kaolinite particles.…”
Section: Introductionmentioning
confidence: 99%